Strain behaviour in composite plate girders with imperfect shear connection - Mohd Yazmil Md Yatim,; Nandivaram E. Shanmugam, (Penerbit Universiti Kebangsaan Malaysia, 2016)
This paper is concerned with the experimental study on the behaviour of strain in steel-concrete composite plate girders having imperfect shear connection. A number of slender girders of practical size were loaded to failure under shear applied at the mid-span. The main variables considered in this study are the longitudinal spacing of stud connector, diameter of stud shank, number of studs along the upper flange and concrete strength. Strains were measured extensively at specified load levels and locations across the concrete slab width and across the whole depth of the girder. The test results have shown variations of strain from girder to girder due to effects of reaction at supports, compression and tension parts of the girders as well as imperfection in the shear connection. Strains across the slab width show arbitrary respond with maximum tension and compression values of 4284μɛ and 4622μɛ, respectively. Across the girder depth, girders with low degree of shear connection display high step change to the extent of 736μɛ due to incompatibility between two strains at the interface. Slip strain is found maximum near the mid-span of the girders in all cases.